(untitled) - K.C Arun; Muhammad Haroon; Mubashir Ali; Ghazala Naseer (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
It is very important to increase the productivity of agricultural techniques to improve yields and cost reduction in today?s era. Internet of things can make efficient agricultural and farming industry processes by overcoming human involvement in a particular task through automation. Rice is stable food for Pakistan and main exports to national and international market. For the production of high quality rice, there are many factors that affects. Environmental factors like temperature, rainfall, humidity etc are important for the productivity of best quality crops. In this paper we will present IoT based techniques for rice disease prevention. We will present some well-known rice diseases along with their solutions. IoT techniques in soil science, crop protection and prevention are very important for agriculture.Furthermore, we will tabularize the IoT based efforts that are taken for rice disease prevention.